Diseases and Deterioration of Bamboos in India - Shukla, A. N.; Singh, Sujan; Sehgal, H. S. (Indian Forester, 1988)
This paper is a review of the work done on fungi associated with the roots, rhizome, stem, culm and foliage of different species of bamboos occurring in India and the diseases and deterioration caused by them.